Tumor Microenvironment: Extracellular Matrix Alterations Influence Tumor Progression - Brassart-Pasco, Sylvie; Brézillon, Stéphane; Brassart, Bertrand; Ramont, Laurent; Oudart, Jean-Baptiste; Monboisse, Jean Claude (Frontiers in Oncology, 2020)
Tumor microenvironment is composed of various cell types embedded in an altered extracellular matrix (ECM). ECM serves not only as a support for tumor cell but also regulates cell-cell or cell-matrix cross-talks. Alterations in ECM may be induced by hypoxia and acidosis, by oxygen free radicals generated by infiltrating inflammatory cells or by tumor- or stromal-cell-secreted proteases. A poorer diagnosis for patients is often associated with ECM alterations. Tumor ECM proteome, also named cancer matrisome, is strongly altered and different ECM protein signatures may be defined to serve as prognostic biomarkers. Collagen network reorganization facilitates tumor cell invasion. Proteoglycan expression and location are modified in tumor microenvironment and affect cell invasion and metastatic dissemination. ECM macromolecule degradation by proteases may induce the release of angiogenic growth factors but also the release of proteoglycan-derived or ECM protein fragments, named matrikines or matricryptins. This review will focus on current knowledge and new insights in ECM alterations, degradation and reticulation through crosslinking enzymes, on the role of ECM fragments in the control of cancer progression and their potential use as biomarkers in cancer diagnosis and prognosis.